(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2019)
Forests ecosystems are among the most productive terrestrial ecosystems for rural livelihood and environmental conservation. Thus, this study examined the effects of quarry dust on soil properties and on early growth of two hardwood tree species (Gmelina arborea and Terminalia ivorensis).The rock dust was collected from three randomly selected quarry sites in Ondo State, Nigeria at the crushing point while topsoils were collected at 50m and 100m away from the crushing point and from the adjoining forests for laboratory analyses. Ten seeds of each species were procured and planted using four different mixing ratios of the topsoil and quarry dust (0:100, 25:75, 50:50, 75:25, 100:0). The seedlings were nurtured for three months but measurement of stem height, number of leaves and stem diameter commenced at the fouth week. Dry biomass and its carbon and carbon dioxide equivalent were also obtained. The results showed that the samples had high proportion of sand and silt but small amount of clay. Their pH varied between 4.86 and 7.33. The sodium (Na), phosphorus (P), organic carbon, organic matter and nitrogen (N) concentrations were lower at the crushing point than the samples from 50 and 100m away. But the potassium (K) and calcium (Ca) concentrations were higher at the crushing point. Significant differences were observed among the sowing media with regards to seedling growth characteristics. For seed germination, 25:75 rock dust: topsoil was the best medium as it produced mean seed germination of 80%. The 100% rock dust gave the least seed germination potential. The highest numbers of leaves (21 and 6), stem diameter (5mm and 0.6mm) and stem height (32.3cm and 5.7cm) for G. arborea and T. ivorensis respectively, were recorded in 50% rock dust. The growing media significantly influenced the early growth of these two species. Therefore, rock dust could be used for soil amendment management.